Elites in Denmark: Identifying the Elite - Anton Grau Larsen (Copenhagen Business School (CBS), 2015)
Who are the members of the most powerful group in the Danish society? To answer this question, we explored the elite through two different methodological approaches. Using correspondence analysis, we charted the oppositions structuring two exclusive groups, the 100 most important Danish CEOs and the 1,527 elite individuals identified in the Danish Power and Democracy Study in 1999. Through social network analysis, we identified and explored the integration of a core of the power network in Denmark – the power elite - and the inner circle of the corporate elite. The importance of how the elite is defined or identified is discussed in relation with the most widely used method for the study of national elites. With the positional method the size and composition is defined as the data is constructed. We propose a new data sensitive method that identifies a cohesive elite with social network analysis. This lets us analyse the composition and like C.W. Mills identify the key institutional orders in Denmark.
hdl:10398/9512
Keywords: 650